Assessment of the Cannabinoid Content from Different Varieties of Cannabis sativa L. during the Growth Stages in Three Regions. Issue 12 (28th October 2021) - Abdollahi, Mahnaz; Sefidkon, Fatemeh; Peirovi, Afshin; Calagari, Mohsen; Mousavi, Amir
Abstract: Hemp ( Cannabis sativa L.) belongs to the Cannabaceae family. It is very rich in chemical constituents, especially the cannabinoids which has not been reported in any other plant, and has broad pharmacological properties. Hemp as a multi‐purpose crop is a good source of fibers, seed, fixed and volatile oil. It is known that the cannabinoid content of hemp is related to genetic factors, as well as plant's growth stages and environmental factors such as latitude, altitude, weather, particularly moisture availability and nutrient supply during the growing season. The present study was designed to produce hemp that contains allowable concentration of THC (<3 %) by comparing different varieties of hemp, different stages of plant growth, and different geographical locations where it was planted. To achieve this, seeds of two native populations from Iran (Fars and Yazd Provinces) and one foreign variety from France (Fedora17, as an industrial hemp cultivar) with its progenies (Fedora17‐2) were cultivated in 3 research fields (Gilan, Golestan and Alborz provinces) in Iran. The following plant materials were extracted with methanol/chloroform and analyzed by HPLC: foliage in the vegetative stage, inflorescent in the flowering stage, inflorescent of seeds in the seeding stage and the mature seed. The THC concentration of Fedora17 (Fed17) in all three geographical locations was found to be under 0.03 % or even non‐detectable. Same result was also observed in its progenies (Fed17‐2), indicating stability of the trait in this cultivar. The THC concentration of the Yazd variety that was planted in Alborz and Gilan regions was less than 0.080 % in all growth stages. The female flowers planted in Golestan, showed a THC concentration of 1.029 % which was more than the allowed THC concentration of <3 %. The THC concentration in all growth stages of all of the different varieties planted varied from 0 to 1.392 %. The above results indicates that the type of cannabinoid produced depends on the difference in genetic prosperities of the different seed types as well as the growth stage in which the plant material was extracted. On the other hand, the climate and the region in which the seeds were planted had little influence on the THC concentration. Abstract :